As construções daqui vem e daí vem no português contemporâneo - Rocha, Rossana Alves (2011)
Investigation of patterns of usage of daqui vem and daí vem, understood as constructions pairings of form and meaning whose meaning is not only given by the sum of construction members understanding (Croft, 2001). The research is qualitative, based on corpora of the twentieth century and the beginning of XXI. The research is also based in the linguistic funcionalism, according to Traugott and Dasher (2005), Cunha et alli (2003), and others one, from the study of grammaticalization, understood as a process in which a grammatical item or, in our case, sequences of grammatical items tend to regularize and become conventional its meaning, and in the study of metaphorical and metonymic extension mechanisms as well as in the cognitive approach of the construction grammar, especially, in terms of Croft (2001), in the study of the symbolic structure construction. It analyses the meaning and form linking process that derives the alluded constructions, promoting an interpretive analysis of their discourse-pragmatic motivations. This confirms the hypothesis that daqui vem and daí vem, in certain contexts, no longer composed by two independent words, a locative adverb and a full lexical verb, in order to become constructions. This process related to what Traugott and Dasher (2005) called invited inference , due to the fact the speaker/writer makes use of elements originally in the level of grammar, such as the locative pronoun and movement verb, for articulation of another meaning, in order to get the membership and approval of his/her interlocutor. This suggestion of inference is effect of highly interactive strategies subjectivation and intersubjectivation throughout the participants of communicative act perform on each other. Therefore, multiple functions of daqui vem and daí vem are detected. When it was not possible to identify a unique function to daqui vem and daí vem, these data were called imbricated cases. In most of the fragments it was observed besides the most prototypical use of daqui vem, as an adverb and a verb, their use as an argumentative operator in the scope of construction. Daí vem, in turn, shows as grammaticalized arrangement, less referential, the function of sequencer, argumentative operator, articulator of contraexpectative and introducer of topic, and as a not grammaticalized arrangement, more prototypical, the daí element was identified as a sequencer element, an advanced degree of grammaticalization, followed by vem element. Finally, it was recorded, by comparing the mentioned arrangements, the abstracter use of daí vem.